Sympatho-vagal activation during obstructive respiratory events in pigs and blunted atrial arrhythmogenic effects by pharmacological IKACh-inhibition. (19th May 2022) - Linz, B; Hertel, JN; Sattler, SM; Tfelt-Hansen, J; Linz, D; Jespersen, T
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Novo nordisk foundation Background: Obstructive sleep apnea (OSA) is associated with a sympatho-vagal activation which is suspected to create a complex substrate for atrial fibrillation (AF). Purpose: In pigs, we investigated atrial arrhythmogenic consequences of simulated obstructive respiratory events by intermittent negative upper airway pressure (INAP) application and tested antiarrhythmic properties of an atria-specific IK, ACh-inhibitor. Methods: In spontaneously breathing pigs, obstructive respiratory events were simulated by intermittent negative upper airway pressure (INAP) applied via a pressure device connected to the intubation tube. INAP was applied for 75 seconds, every 10 minutes, three times before (vehicle) and two times following infusion of an IK, ACh-inhibitor. P-wave, PQ-duration, atrial effective refractory periods (AERP) and left ventricular hemodynamic parameters (maximum upstroke velocity, minimal downslope velocity and systole duration) were acquired before (Pre-INAP), during (INAP) and after (Post-) INAP. AF-inducibility was determined by a S1S2 atrial pacing protocol. Results: During vehicle infusion, INAP transiently shortened AERP (Pre-INAP: 147±8ms vs. Post-INAP 105±12 ms; p=0.021) and increased AF-inducibility (Pre-INAP: 10±6% vs. Post-INAP 57±15%; p=0.018). Whereas p-wave duration remained stable, PQ-duration prolonged (Pre-INAP: 130±6ms vs. Post-INAP 142±7ms; p=0.03). Left ventricular maximum upstroke velocity increased (Pre-INAP: 1990±118 mmHg/s vs. Post-INAP 3980±704 mmHg/s; p=0.04), minimal downslope velocity decreased and systole duration shortened (Pre-INAP: 236±6 ms vs. Post-INAP 202±12 ms; p=0.04). The IK, ACh-inhibitor increased AERP (vehicle 147±8ms vs. IK, ACh-inhibitor 171±9ms; p=0.05) and sufficiently prevented INAP-associated AERP-shortening (Pre-INAP: 171±9ms vs. Post-INAP 180±9ms; p=0.219) and PQ-duration prolongation (Pre-INAP: 116±8ms vs. Post-INAP 113±7ms; p=0.76). INAP-induced changes of left ventricular maximum upstroke/minimal downslope velocity and systole duration remained unaffected in the presence of the IK, ACh-inhibitor. Conclusion: During obstructive respiratory events simulated by INAP in pigs, left ventricular hemodynamic changes demonstrated elevated sympathetic tone, while atrial electrophysiological parameters resemble elevated parasympathetic tone at the same time. This was associated with increased AF-susceptibility. Pharmacological IK, ACh-inhibition blunted INAP-induced impairment of atrial electrophysiology without affecting left ventricular hemodynamic changes. Hence, pharmacological IKACh-inhibition may constitute a promising treatment strategy in AF-patients with OSA.